Simpang Tiga Tidak Bersinyal Evaluasi Kinerja Simpang Tiga Tak Bersinyal (Studi Kasus Jalan Tlogomas-Jalan Batu Permata Tlogomas Kota Malang) - Bria, Mario Oktovianus; Arifianto , Andy Kristafi; Rahma , Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
Intersection of Jalan Raya Tlogomas-Jalan Raya Batu Permai, Malang City is an unmanned intersection area that has a very large traffic volume and is passed by various types of transportation. There are often long queues of vehicles at the exit point of Batu Permai highway and vice versa, causing congestion on the highway, besides shops and housing that are too close to the road body. So the author chose the location, namely the Jalan Raya Tlogomas section of Malang City, at this intersection there is often congestion which results in the accumulation of vehicles on certain days or hours, it often results in delays, queues and congestion at intersections without a road at that location. The purpose of this study is to determine the existing conditions and performance at the intersection and get alternative solutions in solving the existing problems. The analysis used during this research is along with carrying out direct monitoring in the field and utilizing the Indonesian Road Capacity Manual (MKJI 1997). Based on the results of the analysis, it was found that the intersection capacity did not meet the requirements of MKJI 1997. With DS exceeding the limit along with Queuing Opportunity (QP) > 100%. The solution to be offered is the installation of traffic signs prohibited parking and right turns to prevent excessive delays on each road section so as to solve the case that occurs at the Tlogomas intersection in Malang City.